Design of biopolymer-based hemostatic material: Starting from molecular structures and forms. (15th December 2022) - Zou, Chen-Yu; Li, Qian-Jin; Hu, Juan-Juan; Song, Yu-Ting; Zhang, Qing-Yi; Nie, Rong; Li-Ling, Jesse; Xie, Hui-Qi
Abstract: Uncontrolled bleeding remains as a leading cause of death in surgical, traumatic, and emergency situations. Management of the hemorrhage and development of hemostatic materials are paramount for patient survival. Owing to their inherent biocompatibility, biodegradability and bioactivity, biopolymers such as polysaccharides and polypeptides have been extensively researched and become a focus for the development of next-generation hemostatic materials. The construction of novel hemostatic materials requires in-depth understanding of the physiological hemostatic process, fundamental hemostatic mechanisms, and the effects of material chemistry/physics. Herein, we have recapitulated the common hemostatic strategies and development status of biopolymer-based hemostatic materials. Furthermore, the hemostatic mechanisms of various molecular structures (components and chemical modifications) are summarized from a microscopic perspective, and the design based on them are introduced. From a macroscopic perspective, the design of various forms of hemostatic materials, e.g., powder, sponge, hydrogel and gauze, is summarized and compared, which may provide an enlightenment for the optimization of hemostat design. It has also highlighted current challenges to the development of biopolymer-based hemostatic materials and proposed future directions in chemistry design, advanced form and clinical application. Graphical abstract: Image 1 Highlights: Biopolymers possess sound biocompatibility, biodegradability and bioactivity for the design of hemostatic materials. Molecular structure designs including component and chemical modification are summarized from a microscopic perspective. Design of various forms of hemostatic materials is discussed and compared synthetically from a macroscopic perspective.